Proses Morfologis dalam Kumpulan Puisi Asmaraloka: Puisi, Nada, dan Cinta Karya Usman Arrumy - Sitatur Rohmah; I Wayan Simpen; I Wayan Teguh (Udayana University, 2023)
This research is entitled The Morphological Process in the Poetry Collection Asmaraloka: Puisi, Nada, dan Cinta by Usman Arrumy. This study aims to describe (a) the types of affixation in the poetry collection Asmaraloka: Puisi, Nada, dan Cinta by Usman Arrumy, (b) the types of reduplication in the poetry collection Asmaraloka: Puisi, Nada, dan Cinta by Usman Arrumy, and (c) types of compounding in the poetry collection Asmaraloka: Puisi, Nada, dan Cinta by Usman Arrumy. This type of research is a qualitative research with the data source in the form of a collection of poetry. The data collection methods and techniques used in this research are the note-taking method, the data analysis method and technique used is the agih method with basic techniques in the form of techniques for direct elements, as well as methods and techniques for presenting the results of data analysis in the form of formal informal methods with techniques descriptive. The results of this study include types of affixation in the form of prefixes meng- totaling 138 data, ber- totaling 61 data, di- totaling 21 data, ter- totaling 34 data, se- totaling 31 data, ke- totaling 2 data, pe- totaling 3 data, peng- totaling 8 data; the suffix –an is 26 data, -kan is 12 data, -nya is 1; infix –em- is 1; simulfixes peng-...-an totaling 6 data, per-...-an totaling 8 data, se-...-nya totaling 4 data, ke-...-an totaling 38 data. The reduplication and compounding found respectively amounted to 17 and 19 data. Apart from the result of the morphological process, there are also typical lexemes found in the data source, namely membayang, menyuar, mendamba, melindap, bertubir, diperam, and dijerang. These lexemes are markers of the uniqueness of the poetry Asmaraloka: Puisi, Nada, dan Cinta by Usman Arrumy.